Extreme value statistics of the halo and stellar mass distributions at high redshift: are JWST results in tension with ΛCDM?. Issue 2 (11th November 2022) - Lovell, Christopher C; Harrison, Ian; Harikane, Yuichi; Tacchella, Sandro; Wilkins, Stephen M
ABSTRACT: The distribution of dark matter halo masses can be accurately predicted in the lambda cold dark matter (ΛCDM) cosmology. The presence of a single massive halo or galaxy at a particular redshift, assuming some baryon and stellar fraction for the latter, can therefore be used to test the underlying cosmological model. A number of recent measurements of very large galaxy stellar masses at high redshift ( z > 8) motivate an investigation into whether any of these objects are in tension with ΛCDM. We use extreme value statistics to generate confidence regions in the mass–redshift plane for the most extreme mass haloes and galaxies. Tests against numerical models show no tension, neither in their dark matter halo masses nor their galaxy stellar masses. However, we find tentative >3σ tension with recent observational determinations of galaxy masses at high redshift from both Hubble Space Telescope and James Webb Space Telescope, despite using conservative estimates for the stellar fraction ( f ⋆ ∼ 1). Either these galaxies are in tension with ΛCDM, or there are unaccounted for uncertainties in their stellar mass or redshift estimates.